1993
DOI: 10.1111/j.1529-8817.1993.tb00152.x
|View full text |Cite
|
Sign up to set email alerts
|

MOLECULAR ANALYSIS REVEALS CRYPTIC DIVERSITY IN PORPHYRA (RHODOPHYTA)1

Abstract: The small subunit ribosomal RNA (SSU rRNA) gene was amplified from 15 species of the red alga Porphyra and digested with restriction enzymes to generate data for species identification. The subset of species selected for phylogenetic analysis was P. cuneiforms (Setchell et Hus) Krishnamurthy, P. nereocystis anderson, P. schizophylla Hollenberg et Abbott, P. thuretii Setchell et Dawson and Porphyra 1674. Bangia sp. was used as an out‐group. Restriction sites were mapped and used as characters in parsimony and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0
2

Year Published

1995
1995
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(50 citation statements)
references
References 47 publications
1
47
0
2
Order By: Relevance
“…In relation to Porphyra, RFLP (restriction fragment length polymorphism) analysis of the small subunit ribosomal RNA (SSU rRNA) gene has been used to distinguish between species of Porphyra from the Pacific coast of North America (Stiller & Waaland, 1993). The use of molecular, morphological and reproductive evidence to distinguish between species illustrates the value of a holistic approach…”
Section: Discussionmentioning
confidence: 99%
“…In relation to Porphyra, RFLP (restriction fragment length polymorphism) analysis of the small subunit ribosomal RNA (SSU rRNA) gene has been used to distinguish between species of Porphyra from the Pacific coast of North America (Stiller & Waaland, 1993). The use of molecular, morphological and reproductive evidence to distinguish between species illustrates the value of a holistic approach…”
Section: Discussionmentioning
confidence: 99%
“…In some of these cases, other kinds of differences had been noted prior to genetic studies (e.g. Brodie et al, 1996;Blomster et al, 1998), while, in other cases the genetic identification of cryptic species came as a complete surprise (Stiller & Waaland, 1993;Benzie et al 1997;Pillman et al, 1997). Not all cryptic species are highly divergent genetically, however (Brodie et al, 1996), and genetic data have also been used to synonymize morphotaxa (Lindstrom & Cole, 1992;Blomster et al, 1998).…”
Section: Multicellular Plantsmentioning
confidence: 99%
“…Genera recently examined using genetic techniques include Porphyra (Lindstrom & Cole, 1992;Stiller & Waaland, 1993;Brodie et al, 1996), Phycodris (Van Oppen et al, 1995a,b), Gracilariopsis (Goff et al, 1994), Gracilaria (Goff et al, 1994), Pikea (Maggs & Ward, 1996), Cladophora (Bakker et al, 1995a,b), Caulerpa Pillmann et al, 1997;Olsen et al, 1998) and Enteromorpha (Blomster et al, 1998). These taxa include economically important species (Porphyra, Gracilaria, Gracilariopsis), as well as bioindicators of pollution (Enteromorpha) and pest species (Caulerpa).…”
Section: Multicellular Plantsmentioning
confidence: 99%
“…raulaguilarii mentioned here. Table 2 shows the vegetative and reproductive characters of various species of Pyropia and in it observed the (Stiller & Waaland 1993, Oliveira et al 1995, Broom et al 1999, Kunimoto et al 1999 have revealed considerable interspecies diversity of the nrSSU and rbcL regions within this genus and suggest that provides useful characters for species identification.…”
Section: Discussionmentioning
confidence: 99%